English Language Training Programme for Indonesian Toursim Drivers: A Report on English Language Teaching in Makassar - Burhanuddin Burhanuddin; Ratnawati Ratnawati; Andi Hudriati (ELT Worldwide: Journal of English Language Teaching, 2021)
Training on the Use of Basic English for tourism drivers in South Sulawesi aims to improve English language skills for each trainee. This is relevant to tourism development which is one of the development sectors currently being promoted by the government. South Sulawesi has various tourism potentials, including natural and cultural attractions. More and more foreign tourists visit this area and they are guests who must be served well, therefore participants must be able to communicate in English with the tourists, so that tourists feel happy, but the fact is that there are still many tourism drivers who cannot communicate in English and they only use gestures, even though they have a big share and contribution to the development of tourism. During the English training, the participants were stimulated using lectures, role plays, question and answer and demonstrations. Training activities for tourism drivers are carried out for 2 and a half months. The English materials provided include various conversations and vocabulary which include: Alphabet, Parts of Speech, Countries & Nationalities, at the hotel, at the bank / money changer, places & direction, at the post office, at the tourist objects and so on. This training also produces training modules that are printed and distributed to all participants. Although it is still in simple form, it is hoped that this module will be useful for further training. This community service activity can be concluded that it has been successfully implemented, this is evidenced by the suitability of the material with the needs, active participation and high motivation of the participants who are expected to provide maximum service and indirectly introduce and promote tourism potential in South Sulawesi, according to With the target to be achieved from this training, determine the quality of public transportation services through tourism drivers so that they can have intensive conversations with both domestic and foreign tourists.